2007
DOI: 10.1016/j.compstruct.2006.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Particle swarm optimization approach for multi-objective composite box-beam design

Abstract: Abstract:-This paper presents a multi-agent search technique to design an optimal composite box-beam helicopter rotor blade. The search technique is called particle swarm optimization ('inspired by the choreography of a bird flock'). The continuous geometry parameters (cross-sectional dimensions) and discrete ply angles of the box-beams are considered as design variables. The objective of the design problem is to achieve a) specified stiffness value and b) maximum elastic coupling. The presence of maximum elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 30 publications
2
46
0
3
Order By: Relevance
“…Such particles will fastly trend to the better searching space. Basing the above idea, this paper proposes a method which using Logistics function to adjust inertia factor [4].…”
Section: Chaos Pmo Algorithm Optimized By Logistic Functionmentioning
confidence: 99%
“…Such particles will fastly trend to the better searching space. Basing the above idea, this paper proposes a method which using Logistics function to adjust inertia factor [4].…”
Section: Chaos Pmo Algorithm Optimized By Logistic Functionmentioning
confidence: 99%
“…PSO gained increasing popularity in recent years due to its ability to solve efficiently and effectively a plethora of problems in science and engineering. PSO has been effectively used in a variety of data mining and optimization problems from power systems to composite beam structures and from medicine to operation research problems [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Such problems are characterized by discontinuities, lack of derivative information, noisy function values and disjoint search spaces [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Kradinov et al (2007) showed the application of genetic algorithm in the optimal design of bolted composite lap joints. Moreover, Suresh et al (2007) investigated the particle swarm optimization approach for multi-objective composite boxbeam design. Kathiravan and Ganguli (2007) showed the application of particle swarm optimization and gradient method in the strength design of composite beams.…”
mentioning
confidence: 99%